CURRICULUM NEEDS ANALYSIS FOR ENGLISH EDUCATION STUDENTS: TOWARD A RESPONSIVE AND TECHNOLOGY-INTEGRATED FRAMEWORK - Indahyanti, Rizka; Rahman, Ali Wira (Lembaga Jurnal FKIP Universitas Bosowa, 2025)
This study investigates the curriculum of the English Education Department at FKIPS Universitas Islam Makassar (UIM) through a comprehensive needs analysis aimed at enhancing its relevance and responsiveness. Using mixed methods, data were collected from 24 students, 4 lecturers, and 8 English teachers through questionnaires and semi-structured interviews. The findings reveal that students prefer kinaesthetic and visual learning styles and show a strong inclination toward technology-enhanced instruction, including video-based and app-supported learning. Teachers and lecturers highlighted challenges such as student motivation, classroom management, and the integration of educational technology. Based on the results, several curriculum recommendations were made: incorporating flexible, tiered modules; expanding interactive, hands-on learning activities; and emphasizing technology integration through frameworks like TPACK. New courses, such as English for Specific Purposes (ESP), and updated assessment methods, including project-based and continuous evaluations, were also proposed. These recommendations aim to align the curriculum with modern teaching trends, national qualification standards, and industry expectations. Ultimately, the revised curriculum is expected to better equip graduates with the skills needed in 21st-century educational and professional environments, ensuring that FKIP UIM remains at the forefront of English language teacher education in Indonesia